The Jewish state : a century later - Dowty, Alan, 1940- (University of California Press, 1998)
The Jewish State is a comprehensive interpretative study of the historical roots and contemporary functioning of Israel. Nationhood and democracy have not unfolded in a social or political vacuum, but instead developed from pre-state Jewish traditions in Palestine and in Eastern Europe. Dowty elucidates a broad cluster of cultural, historical, and ideological tenets that have come to comprise the infrastructure of the contemporary political system. His analysis provides a new interpretation of the formation and development of the Israeli nation. This book will prove invaluable for students, scholars, and general readers looking for one book that will give them an intelligent overview of the Jewish state.